2021
DOI: 10.1021/acsnano.0c08429
|View full text |Cite
|
Sign up to set email alerts
|

MX Anti-MXenes from Non-van der Waals Bulks for Electrochemical Applications: The Merit of Metallicity and Active Basal Plane

Abstract: Two-dimensional transition-metal compounds (2DTMCs) are promising materials for electrochemical applications, but 2DTMCs with metallicity and active basal planes are rare. In this work, we proposed a simple and effective strategy to extract 2DTMCs from non-van der Waals bulk materials and established a material library of 79 2DTMCs, which we named as anti-MXenes since they are composed of one M atomic layer sandwiched by two X atomic layers. By means of density functional theory computations, 24 anti-MXenes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 108 publications
(172 reference statements)
4
35
0
Order By: Relevance
“…These anti-MXenes are demonstrated as excellent electrode materials for HER activity because of their metallicity and an active basal plane. 234 As shown in Fig. 7c, CoP, CoB, CoSi and FeB exhibit excellent HER at some specific H coverages, while CuS can enhance the HER in the whole range of H coverages, while noble-metal free anti-MXenes show favorable H-binding.…”
Section: Energy Storage Applicationsmentioning
confidence: 79%
See 1 more Smart Citation
“…These anti-MXenes are demonstrated as excellent electrode materials for HER activity because of their metallicity and an active basal plane. 234 As shown in Fig. 7c, CoP, CoB, CoSi and FeB exhibit excellent HER at some specific H coverages, while CuS can enhance the HER in the whole range of H coverages, while noble-metal free anti-MXenes show favorable H-binding.…”
Section: Energy Storage Applicationsmentioning
confidence: 79%
“…The choice of surface termination was predicted under varying pH values with different electrode potentials and it was found that the -O terminal group is energetically preferable for Nb 2 C and Nb 4 C 3 , while the mixture of -O and -OH groups is favorable for Ti 2 C, Ti 3 C 2 and V 2 C MXenes. 219 Recently Jinxing et al 234 proposed an effective and simple stratagem for anti-MXenes made of one M atomic layer sandwiched between two X atomic layers (see Fig. 7b).…”
Section: Energy Storage Applicationsmentioning
confidence: 99%
“…The reaction mechanism information can be obtained by simulating these reaction processes, and the intrinsic information such as bandgap, energy, and bond length can be obtained by calculating the electronic structure. [128,[208][209][210] From this information, we can predict the physical and chemical properties of the materials.…”
Section: Machine Learning and Theoretical Computationmentioning
confidence: 99%
“…In a recent study, 20 Jinxing et al discovered a new class of materials called anti-MXenes, with promising electrochemical and catalytic applications. They studied about 79 anti-MXene materials and found that around 24 anti-MXene materials are stable.…”
Section: Introductionmentioning
confidence: 99%